Characterization of oyster mushroom-soy protein meat analog using single-screw extruder with extrusion variables - Mohamad Mazlan, Mazween (2021)
The most difficult aspects of the meat analog extrusion are attaining desirable product’s appearance and texture. Using a single-screw extruder and incorporating low-grade oyster mushroom into soy proteins can produce a fibrous-structured meat analog. Thus, three research objectives of this study were to determine suitable extrusion process parameters range (barrel temperature and screw speed). Next, evaluate the effects of different screw speeds and oyster mushroom (OM) addition on the meat analog’s physical, microstructure, and textural characteristics. Then, model the effect of screw speed and OM addition on the extrusion specific mechanical energy (SME). Satisfactory extrudates were obtained at a barrel temperature of 140 °C, screw speed range of 100 rpm - 160 rpm, and OM addition at 0%, 7.5%, and 15% via factorial experiments. Single-screw extrusion equipped with a slit die successfully produced expanded oyster mushroom-soy protein extrudates. However, the increase in the OM content significantly decreased (p ≤ 0.05) the expansion ratio of the extrudate from 1.26 to 0.98. This result indicated that adding more OM restrained the expansion ratio. The extrudates had a medium density range (maximum of 1393.70 ± 6.30 kg/m3). By adding OM, the extrudates attained a higher moisture content (range = 34.77% to 37.93%) than the extrudates containing the protein mixture only (range = 26.99% to 32.33%). The increase in screw speed and OM significantly increased (p ≤ 0.05) the water absorption index. The increase in the texturization index was significantly influenced (p ≤ 0.05) by OM addition rather than the screw speed. A defined fibrous structure supported the high texturization index and small shape of air cells observed in the extrudates. The effect of screw speed and OM addition on the texture characteristics (hardness, gumminess, and chewiness) and SME was determined via factorial experiment design. Compared with the effect of OM addition, the impact of individually increased screw speeds was minimal. However, the combined effects of screw speed and OM addition had significantly reduced (p ≤ 0.05) all the texture characteristics. The hardness (3521.35 g) and gumminess (2717.85) of the meat analog extruded at the maximum screw speed (160 rpm) and 15% OM addition are close to the chicken breast characteristics, respectively. The oyster mushroom–soy protein extrudates are chewier compared to the non-extruded texturized vegetable protein (TVP) and chicken meats. The SME values of the single-screw extrusion were linearly affected by the increasing screw speeds, which also lies in the adequate range (< 200 kJ/kg) for meat analog production. Applying the superposition technique successfully shifted the individual linear curves of the SME into a smooth master curve. The relationship of screw speeds and SME can be observed to describe the extruder’s performance in the production of oyster mushroom-soy protein meat analogs. These findings suggest that oyster mushroom-soy protein meat analogs with satisfying appearance, physical and texture characteristics are best produced via single-screw extrusion at a barrel temperature of 140 °C, screw speed of 160 rpm, and 15% OM addition.